The Relationship between Inequality and Growth: Evidence from New Data - Costanza Naguib (Swiss Journal of Economics and Statistics, 2017)
The relationship between inequality and growth has attracted a lot of attention in the previous literature. Estimation of this relationship may be biased by simultaneity, omitted variables and measurement error. The present paper contributes to the existing work by introducing the wealth Gini coefficient as a new inequality measure. The most reliable and recent data on income inequality are used for estimation. We employ the Arellano-Bond GMM estimation technique and we find that there seems to be a positive relationship between wealth inequality and real per capita GDP growth, but this relationship is not robust to different model specifications.
Keywords: D30; O40; 330; income inequality; wealth inequality; Gini coefficient; economic growth; dynamic panel data; GMM estimation